Expression of individualism – collectivism in verbal insults - Курапов, Антон; Іщенко, Олександр; Тєльчаров, Олександр (Київський національний університет імені Тараса Шевченка, 2017)
Abstract It is well known that many cultures in the modern world are characterized by such polar constructs as individualism and collectivism.Western world is generally perceived as much more individualistic, on the contrary, Eastern world is perceived as much more collectivistic.However, civilizational identity of Ukraine is not sufficiently defined due to the specific historical development, since it has always been between East and West. Semin and Rubini (1990) proposed a study of the manifestations of individualism and collectivism through the analysis of verbal abuse that are common for a specific nationality. In our opinion, this method will identify the most current tendency for Ukrainians. For comparison, the results of a study conducted in Finland, Sweden and Poland were also presented. Thus, according to a study, Ukrainians are more likely to express individualism in 3 comparison to the expression of collectivism. The same applies to other studied groups.

Відомо що багато культур у сучасному світі характеризуються популярними конструктами індивідуалізм та колективізм. Західні культури зазвичай сприймаються як більш індивідуалістичні, проте культури сходу сприймаються як більш колективістські. Незважаючи на це, цивілізаційна ідентичність України залишається невизначеною у зв'язку зі специфічним історичним розвитком так як вона завжди знаходилася на перетині Сходу та Заходу. Семін та Рубіні (1990) запропонували дослідження, де індивідуалізм та колективізм визначалися через аналіз вербальних обрáз. На нашу думку, їхній метод допоможе також визначити сучасну специфіку населення України. Для порівняння були взяті респонденти із Польщі, Фінляндії та Швеції. Українці, так як і інші респонденти, виявили схильність до прояву індивідуалізму.
Вираження індивідуалізму – колективізму у вербальних образах
Keywords: індивідуалізм; колективізм; культурні синдроми; вербальні обрáзи; individualism; collectivism; cultural syndromes; verbal abuse